Multilayer current collector and preparation method and application thereof

By adopting an optimized composite metal layer structure in the multi-layer current collector, the problems of high internal resistance, poor adhesion and interlayer structural defects in the battery in the prior art are solved, and its bending resistance and cycle life of the battery are significantly improved.

CN120149423AActive Publication Date: 2025-06-13YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510300389.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-06-13
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

The existing multi-layer current collectors have high internal resistance, poor adhesion and interlayer structural defects in the battery, which affects its mechanical properties and bending resistance.

Method used

A composite metal layer is adopted, including a laminated current collector layer and an aluminum layer. The current collector layer is located between the base layer and the aluminum layer. The resistivity and crystal surface relative texture coefficient of the aluminum layer are optimized to improve density and bending resistance.

Benefits of technology

By optimizing the resistivity of the composite metal layer and the crystal surface structure of the aluminum layer, the bending resistance of the multi-layer current collector is significantly improved, so that the minimum number of light transmission after n bent times exceeds 100 times, thereby improving the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005311705770000021
    Figure BDA0005311705770000021
  • Figure BDA0005311705770000091
    Figure BDA0005311705770000091
  • Figure BDA0005311705770000101
    Figure BDA0005311705770000101
Patent Text Reader

Abstract

The invention specifically discloses a multi-layer current collector and a preparation method and application thereof. The multi-layer current collector comprises a substrate layer and composite metal layers which are sequentially arranged on the surface of at least one side of the substrate layer in a stacked mode, each composite metal layer comprises a current collection layer and an aluminum layer which are arranged in a stacked mode, and the current collection layer is located between the substrate layer and the aluminum layer; and the resistivity rho of the composite metal layer on any side surface of the multi-layer current collector meets the condition that rho is greater than 2.7 omega.m and less than or equal to 3.1 omega.m. The multi-layer current collector has the advantages that the defects of the multi-layer current collector structure are reduced, and the anti-bending performance of the multi-layer current collector is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of current collectors, and in particular to a multi-layer current collector and its preparation method and application. Background Art

[0002] With the rapid development of new energy and advanced manufacturing industries, it is urgent to improve the key performance of batteries such as cycle life, safety performance, and energy density. The current collector is a key component in the battery, which plays a role in collecting current. At the same time, the quality of the current collector performance will directly affect the technical indicators such as the cycle life, energy density, and safety of the battery.

[0003] Currently, the common positive and negative current collectors in the battery industry are mostly made of copper foil and aluminum foil. The current collector made of pure metal has high cost and quality. At the same time, its performance in battery safety and anti-bending performance is often not satisfactory. With the continuous development of the current collector technology field, the multi-layer current collector gradually replaces the pure metal current collector and plays a role in the battery field due to its advantages in safety, energy density, and cost control.

[0004] The multi-layer current collector usually includes two metal layers and a substrate sandwiched between the two metal layers. The currently known methods for setting the metal layer include electroplating, evaporation plating (physical vapor deposition), chemical deposition, magnetron sputtering, bonding, coating compounding, etc.; however, since the substrate in the multi-layer current collector is mostly a polymer film, this will increase the internal resistance of the battery to a certain extent. In addition, the adhesion between the metal layer and the substrate in the multi-layer current collector is poor, and there may also be interlayer structure defects during the coating process, which is not conducive to the improvement of the mechanical properties and anti-bending performance of the multi-layer current collector. Summary of the Invention

[0005] In order to solve the problems in the prior art, the present application provides a multi-layer current collector and its preparation method and application.

[0006] In the first aspect, the present application provides a multi-layer current collector, adopting the following technical solution:

[0007] A multi-layer current collector includes a base layer and a composite metal layer provided on at least one surface of the base layer. The composite metal layer includes a current collecting layer and an aluminum layer arranged in a stacked manner, and the current collecting layer is located between the base layer and the aluminum layer;

[0008] Wherein, the resistivity ρ of the composite metal layer on any surface of the multi-layer current collector satisfies 2.7 Ω·m < ρ ≤ 3.1 Ω·m.

[0009] In this application, by selecting a composite metal layer with the above resistivity value, the grains in the composite metal layer are finer, with fewer pores or defects, and higher density. Moreover, the inventor's research found that the composite metal layer with the above resistivity value range is more conducive to improving the bending resistance of the current collector when combined with the base layer. This may be because the dense structure in the composite metal layer can make the material more uniform internally, and it is not easy to break due to the expansion of defects during bending. In addition, the dense structure in the composite metal layer can better resist external stress, thereby improving the bending resistance of the current collector, making the minimum number of times of light transmission after bending n times > 100 times, and further increasing the cycle life of the battery.

[0010] Preferably, the relative texture coefficient (RTC) of the <200> crystal plane of the aluminum layer is 30% - 60%.

[0011]

[0012] represents the experimental diffraction intensity of the <200> crystal plane of the aluminum layer;

[0013] represents the standard diffraction intensity of the <200> crystal plane of the aluminum layer;

[0014] I hkl represents the experimental diffraction intensity of any crystal plane of the aluminum layer in the XRD pattern;

[0015] represents the standard diffraction intensity of any crystal plane of the aluminum layer;

[0016] represents the sum of the ratios of the experimental diffraction intensity to the standard diffraction intensity of all crystal planes of the aluminum layer.

[0017] The inventor's research found that by controlling the value of the relative texture coefficient (RTC) of the <200> crystal plane of the aluminum layer, the bending resistance of the multi-layer current collector can be further improved. This is because by adjusting the resistivity of the composite metal layer and the relative texture coefficient of the <200> crystal plane of the aluminum layer, the synchronous optimization of the material microstructure and stress distribution can be achieved. On the one hand, the optimized crystal plane orientation makes the stress distribution more uniform, and the optimized microstructure reduces the number of defects in the aluminum layer. The two work together to enable the aluminum layer to better withstand stress during bending. On the other hand, the two work together to affect the movement and deformation mechanism of dislocations, enabling the aluminum layer to achieve plastic deformation through dislocation movement during bending and resist further deformation through strain hardening. In addition, the regulation of the crystal plane orientation enhances the interface stability between layers, and the regulation of resistivity optimizes the overall microstructure, making the aluminum layer have both good interface bonding strength and optimized microstructure during bending, thereby further improving the overall bending resistance of the multi-layer current collector.

[0018] Preferably, the aluminum layer comprises a first element, the first element comprises at least one of magnesium, calcium, chlorine, and nickel, and the mass proportion of the first element in the aluminum layer is 0.1%-1%.

[0019] By adding the first element to the aluminum layer, the tensile strength of the composite metal layer can be further improved, and the situation of cracks appearing in the multi-layer current collector during the bending process can be avoided.

[0020] Preferably, the aluminum layer comprises a first sub-aluminum layer, a second sub-aluminum layer, and a third sub-aluminum layer which are stacked, and the first sub-aluminum layer is close to the current collector layer;

[0021] Among them, the resistivity of the first sub-aluminum layer and the resistivity of the third sub-aluminum layer are both greater than the resistivity of the second sub-aluminum layer;

[0022] 10%×the thickness of the aluminum layer ≤ the thickness of the second sub-aluminum layer < the thickness of the first sub-aluminum layer;

[0023] 10%×the thickness of the aluminum layer ≤ the thickness of the second sub-aluminum layer < the thickness of the third sub-aluminum layer.

[0024] In this application, by setting the outer metal layer to have a lower density but a thicker thickness, most of the stress can be absorbed and dispersed during the bending process, while the second sub-aluminum layer has a high density and a thin thickness and can provide high-strength support; during the bending process, the second sub-aluminum layer can act as a "buffer layer" to prevent the micro-cracks of the outermost metal layer (the third sub-aluminum layer) from spreading to the inner layer (the first sub-aluminum layer), and finally synergistically improve the bending resistance of the overall structure; in addition, the interfaces of the multi-layer structure can disperse stress and reduce the crack propagation path, which can significantly improve the crack resistance and ductility of the multi-layer current collector.

[0025] Preferably, the thickness of the aluminum layer is 0.2-5 μm; preferably, the thickness of the aluminum layer is 0.8-2 μm.

[0026] Preferably, the thickness of the current collector layer is 1%-10% of the thickness of the aluminum layer; the material of the current collector layer comprises at least one of aluminum, aluminum alloy, nickel, nickel alloy, chromium, chromium alloy, silver, silver alloy, titanium, and titanium alloy.

[0027] Preferably, the material of the base layer comprises at least one of polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polyethylene naphthalate (PEN), poly(p-phenylene terephthalamide) (PPTA), polyimide (PI), polycarbonate (PC), polyether ether ketone (PEEK), polyoxymethylene (POM), polyphenylene sulfide (PPS), polyphenylene oxide (PPO), polyvinyl chloride (PVC), polyamide (PA), and polytetrafluoroethylene (PTFE); the thickness of the base layer is 1-10 μm.

[0028] In a second aspect, the present application provides a method for preparing a multi-layer current collector, adopting the following technical solution:

[0029] A method for preparing a multi-layer current collector includes the following steps:

[0030] S1. Generate the current collecting layer on the surface of the base layer through a magnetron sputtering process to obtain a pretreated base layer;

[0031] S2. Generate the aluminum layer on the surface of the pretreated base layer using molten salt electroplating.

[0032] Preferably, the process parameters in the magnetron sputtering process satisfy: the sputtering power is 6 - 20 kW, the background vacuum degree is 3×10 -3 -5×10 -3 Pa, the argon gas flow rate is 60 - 300 sccm, the cooling temperature of the sputtering main roller is -35°C to 0°C, and the winding speed is 5 - 8 m / s.

[0033] Preferably, the molten salt electroplating method includes the following steps:

[0034] A1. Mix AlCl 3 , NaCl, and KCl to obtain a ternary inorganic salt, heat the ternary inorganic salt, and then perform dehydration and electro-removal of impurities treatment to obtain an inorganic molten salt;

[0035] A2. Place the pretreated base layer in the inorganic molten salt for electroplating to generate the aluminum layer on the surface of the pretreated base layer.

[0036] Preferably, in A1, the mass ratio of AlCl 3 , NaCl, and KCl in the ternary inorganic salt is (6 - 10):(1 - 2):(1 - 2); the temperature for heating the ternary inorganic salt is 100 - 300°C; dehydration treatment is performed using dry HCl gas; the current density during the electro-removal of impurities process is 4 - 30 mA·cm -2 .

[0037] Preferably, in A2, when the pretreated base layer is placed in the inorganic molten salt, the temperature during the electroplating process is 100 - 200°C, and the current density during the electroplating process is 10 mA·cm -2 -150 mA·cm -2 .

[0038] In the present application, the resistivity of the aluminum layer is adjusted by adjusting the concentration of aluminum ions in the inorganic molten salt system and the current density during the electroplating process. When the concentration of aluminum ions in the inorganic molten salt system is relatively high and the current density during the electroplating process is relatively small, it is helpful to prepare an aluminum layer with low resistivity.

[0039] In a third aspect, the present invention provides a pole piece, adopting the following technical solution:

[0040] A pole piece includes the above-mentioned multi-layer current collector and electrode active material located on the multi-layer current collector. Specific embodiments

[0041] For better understanding and implementation, the technical solutions of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments.

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which this application belongs. The terms used in the description of the present application in this specification are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0043] Unless otherwise specified, all numerical values expressing amounts of ingredients, reaction conditions, etc. used in the specification and claims are understood to be modified by the term "about". Therefore, unless otherwise indicated, the numerical parameters set forth herein are approximate values that can vary depending on the desired properties to be obtained.

[0044] As used herein, "and / or" means one or all of the recited elements.

[0045] As used herein, "comprising" and "including" cover cases where only the recited elements are present and cases where there are other unrecited elements in addition to the recited elements.

[0046] All percentages in this application are weight percentages unless otherwise specified.

[0047] Unless otherwise specified, the terms "a", "an", "one" and "the" as used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be contemplated and may be adopted or used in the implementation of the described embodiments.

[0048] Example 1

[0049] A multi-layer current collector includes a base layer and composite metal layers provided on two surfaces of the base layer. The composite metal layer includes a current collecting layer and an aluminum layer arranged in a stacked manner, and the current collecting layer is located between the base layer and the aluminum layer;

[0050] Wherein, the material of the base layer is polyimide, and the thickness of the base layer is 8 μm;

[0051] The material of the current collecting layer is aluminum, and the thickness of the current collecting layer is 120 nm;

[0052] The thickness of the aluminum layer is 1 μm;

[0053] The relative texture coefficient (RTC) of the <200> crystal plane of the aluminum layer is 27%;

[0054] The resistivity ρ of the above composite metal layer is 2.8 Ω·m.

[0055] This embodiment provides a preparation method of the above current collector, and the preparation method includes the following steps:

[0056] S1, perform magnetron sputtering treatment on the base layer (the parameters during magnetron sputtering are controlled as follows: the sputtering power is 10 kW, the background vacuum degree is 4×10 -3 Pa, the argon gas flow rate is 130 sccm, the cooling temperature of the sputtering main roll is -25 °C, and the winding speed is 7 m / min), generate a current collecting layer, and obtain a pretreated base layer;

[0057] S2, take NaCl and KCl and dry them at 300 °C for 5 h, mix AlCl 3 , NaCl, and KCl in a mass ratio of 10:1:1, heat them at 130 °C, introduce dry HCl gas for dehydration, and then perform electro-removing impurities treatment with a current density of 5 mA·cm -2 to obtain an inorganic molten salt;

[0058] S3, place the above pretreated base layer in the above inorganic molten salt, control the electroplating temperature to be 150 °C, and the current density to be 10 mA·cm -2 to obtain an aluminum layer with a thickness of 1 μm, that is, a multi-layer current collector is obtained.

[0059] Example 2

[0060] The difference between this embodiment and Example 1 is that the resistivity ρ of the composite metal layer is 2.9; in step S2 of the preparation method of the current collector, AlCl 3 , NaCl, and KCl are in a mass ratio of 8:1:1, and in step S3, the current density is 20 A·cm -2 , and other steps and parameter settings are the same as those in Example 1.

[0061] Example 3

[0062] The difference between this embodiment and Example 1 is that the resistivity ρ of the composite metal layer is 3.1; in step S2 of the preparation method of the current collector, AlCl 3 , NaCl, and KCl are in a mass ratio of 6:1:1, and in step S3, the current density is 40 A·cm -2 , and other steps and parameter settings are the same as those in Example 1.

[0063] Example 4

[0064] The difference between this example and Example 1 is that the relative texture coefficient (RTC) of the <200> crystal plane of the aluminum layer is 30%, and sodium polydithiopropane sulfonate (SPS) is added to the electroplating solution at a concentration of 1.5 mg / L; other steps and parameter settings are the same as those in Example 1.

[0065] Example 5

[0066] The difference between this example and Example 1 is that the relative texture coefficient (RTC) of the <200> crystal plane of the aluminum layer is 40%; sodium polydithiopropane sulfonate (SPS) is added to the electroplating solution at a concentration of 2 mg / L; other steps and parameter settings are the same as those in Example 1.

[0067] Example 6

[0068] The difference between this example and Example 1 is that the relative texture coefficient (RTC) of the <200> crystal plane of the aluminum layer is 60%; sodium polydithiopropane sulfonate (SPS) is added to the electroplating solution at a concentration of 3.5 mg / L; other steps and parameter settings are the same as those in Example 1.

[0069] Example 7

[0070] The difference between this comparative example and Example 1 is that the relative texture coefficient (RTC) of the <200> crystal plane of the aluminum layer is 70%; sodium polydithiopropane sulfonate (SPS) is added to the electroplating solution at a concentration of 4 mg / L; other steps and parameter settings are the same as those in Example 1.

[0071] Example 8

[0072] The difference between this example and Example 1 is that the aluminum layer includes a first sub-aluminum layer with a thickness of 333 nm, a second sub-aluminum layer with a thickness of 333 nm, and a third sub-aluminum layer with a thickness of 333 nm. The resistivity of the first sub-aluminum layer, the second sub-aluminum layer, and the third sub-aluminum layer is the same, all being 2.8 Ω·m; other steps and parameter settings are the same as those in Example 1.

[0073] Example 9

[0074] The difference between this example and Example 8 is that the aluminum layer includes a first sub-aluminum layer with a thickness of 333 nm, a second sub-aluminum layer with a thickness of 333 nm, and a third sub-aluminum layer with a thickness of 333 nm. For the first sub-aluminum layer, the second sub-aluminum layer, and the third sub-aluminum layer, the resistivity of the first sub-aluminum layer is 2.8 Ω·m, the resistivity of the second sub-aluminum layer is 2.9 Ω·m, and the resistivity of the third sub-aluminum layer is 3.0 Ω·m; other steps and parameter settings are the same as those in Example 8.

[0075] Example 10

[0076] The difference between this example and Example 9 is that the aluminum layer includes a first sub-aluminum layer with a thickness of 333 nm, a second sub-aluminum layer with a thickness of 333 nm, and a third sub-aluminum layer with a thickness of 333 nm. For the first sub-aluminum layer, the second sub-aluminum layer, and the third sub-aluminum layer, the resistivity of the first sub-aluminum layer is 3.0 Ω·m, the resistivity of the second sub-aluminum layer is 2.9 Ω·m, and the resistivity of the third sub-aluminum layer is 2.8 Ω·m; other steps and parameter settings are the same as those in Example 9.

[0077] Example 11

[0078] The difference between this example and Example 9 is that the aluminum layer includes a first sub-aluminum layer with a thickness of 333 nm, a second sub-aluminum layer with a thickness of 333 nm, and a third sub-aluminum layer with a thickness of 333 nm. For the first sub-aluminum layer, the second sub-aluminum layer, and the third sub-aluminum layer, the resistivity of the first sub-aluminum layer is 2.9 Ω·m, the resistivity of the second sub-aluminum layer is 2.8 Ω·m, and the resistivity of the third sub-aluminum layer is 3.0 Ω·m; other steps and parameter settings are the same as those in Example 9.

[0079] Example 12

[0080] The difference between this example and Example 11 is that the aluminum layer includes a first sub-aluminum layer with a thickness of 400 nm, a second sub-aluminum layer with a thickness of 200 nm, and a third sub-aluminum layer with a thickness of 400 nm; other steps and parameter settings are the same as those in Example 11.

[0081] Example 13

[0082] The difference between this example and Example 1 is that magnesium chloride is added to the electroplating solution, and the mass ratio of magnesium in the aluminum layer is 0.5%; other steps and parameter settings are the same as those in Example 1.

[0083] Example 14

[0084] The difference between this comparative example and Example 1 is that nickel chloride is added to the electroplating solution, and the mass ratio of nickel in the aluminum layer is 1%; other steps and parameter settings are the same as those in Example 1.

[0085] Example 15

[0086] The difference between this comparative example and Example 1 is that lanthanum chloride is added to the electroplating solution, and the mass ratio of chlorine in the aluminum layer is 0.1%; other steps and parameter settings are the same as those in Example 1.

[0087] Example 16

[0088] The difference between this comparative example and Example 1 is that magnesium chloride is added to the electroplating solution, and the mass ratio of magnesium in the aluminum layer is 2%; other steps and parameter settings are the same as those in Example 1.

[0089] Example 17

[0090] The difference between this example and Example 5 is that the aluminum layer includes a first sub-aluminum layer with a thickness of 400 nm, a second sub-aluminum layer with a thickness of 200 nm, and a third sub-aluminum layer with a thickness of 400 nm. For the first sub-aluminum layer, the resistivity is 2.9 Ω·m; for the second sub-aluminum layer, the resistivity is 2.8 Ω·m; for the third sub-aluminum layer, the resistivity is 3.0 Ω·m; other steps and parameter settings are the same as those in Example 5.

[0091] Comparative Example 1

[0092] The difference between this comparative example and Example 1 is that the resistivity ρ of the composite metal layer is 4.2; in step S2 of the preparation method of the current collector, the mass ratio of AlCl 3 , NaCl, and KCl is 4:1:1, and the current density in step S3 is 150 A·cm -2 ; other steps and parameter settings are the same as those in Example 1.

[0093] Comparative Example 2

[0094] The difference between this comparative example and Example 1 is that the aluminum layer is prepared by vacuum evaporation. The raw material used in the vacuum evaporation process is high-purity aluminum wire (purity 99.93%), the heating temperature is 1200 °C, and the vacuum degree of the vacuum chamber is 0.1 Pa; other steps and parameter settings are the same as those in Example 1.

[0095] Testing Method

[0096] Sheet Resistance Test: Place the multi-layer current collectors prepared in the above examples and comparative examples on the sample stage, and use a four-probe sheet resistance meter to test the sheet resistance of the samples.

[0097] Elongation Test: Conduct the test in accordance with Standard GB / T 1040.3-2006.

[0098] Resistivity Test: Test the resistivity of the composite metal layer in the multi-layer current collectors prepared in the above examples and comparative examples according to the method specified in GB / T 22638.6-2016 "Test Methods for Aluminum Foil - Part 6: Determination of DC Resistance".

[0099] Bending test: Fix the sample on the bending test device, set the bending angle to 180°, start the bending test, pause after each bending, place the sample on the light transmittance tester to measure the light transmittance. When the number of light-transmitting points within 2 cm exceeds 10 or there is a light-transmitting area with a length exceeding 3 mm, record the bending times corresponding to the situation where the number of light-transmitting points is less than 10 or the length of the light-transmitting points is less than 3 mm, which is the maximum bending times.

[0100] Table 1

[0101]

[0102]

[0103] Combined with Examples 1-3, Comparative Example 1 and Table 1, it can be seen that when the resistivity of the composite metal layer does not meet the limitation (Comparative Example 1), the sheet resistance of the multi-layer current collector increases significantly, and the bending times decrease significantly. This is because at this time, the grains in the composite metal layer are larger, and the number of pores and defects increases, resulting in a decrease in the density of the composite metal layer. The ability of the composite metal layer to resist external stress decreases. At this time, the sheet resistance of the multi-layer current collector formed by the cooperation of the composite metal layer and the base layer increases significantly, and the decrease in the number of bend resistance times is not conducive to optimizing the battery performance.

[0104] Combined with Example 1, Comparative Example 2 and Table 1, it can be seen that by using the molten salt electroplating method to generate an aluminum layer on the surface of the current collecting layer in this application, compared with the operation of using vacuum evaporation to prepare the aluminum layer in Comparative Example 2, it can significantly improve the bonding stability between the composite metal layer and the base layer, and reduce the sheet resistance, resistivity and roughness of the current collector, and increase the number of bend resistance times.

[0105] Combined with Example 1, Examples 4-7 and Table 1, it can be seen that by controlling the relative texture coefficient of the <200> crystal plane of the aluminum layer within the range of 30%-60%, the sheet resistance of the multi-layer current collector can be further reduced and the anti-bending performance can be improved; this is because by controlling the relative texture coefficient of the <200> crystal plane of the aluminum layer, the stress distribution uniformity in the aluminum layer can be further optimized, and the number of defects in the aluminum layer can be reduced, thereby affecting the ability of the aluminum layer to resist deformation during bending and enhancing the interface stability between layers.

[0106] Combined with Example 1, Examples 8 - 12 and Table 1, it can be seen that by adjusting the aluminum layer to include a first sub - aluminum layer, a second sub - aluminum layer and a third sub - aluminum layer, and adjusting the resistivity of the first sub - aluminum layer, the second sub - aluminum layer and the third sub - aluminum layer to be 2.9 Ω·m, 2.8 Ω·m, 3.0 Ω·m respectively, and the thicknesses of the first sub - aluminum layer, the second sub - aluminum layer and the third sub - aluminum layer to be 400 nm, 200 nm, 400 nm respectively, the anti - bending performance of the multi - layer current collector is significantly improved; this is because the layered aluminum layer structure at this time can absorb and disperse most of the stress during the bending process, and can provide high - strength support to prevent the propagation of micro - cracks.

[0107] Combined with Example 1, Examples 13 - 17 and Table 1, it can be seen that by setting a first element in the aluminum layer and controlling the mass ratio of the first element in the aluminum layer to satisfy 0.1% - 1%, the anti - bending strength of the multi - layer current collector can be significantly improved; especially in Example 17, when the aluminum layer is layered and the first element is set in the aluminum layer at the same time, the elongation and the number of bending times of the multi - layer current collector both increase significantly.

[0108] The above embodiments are only used to illustrate the technical solutions of the present application rather than to limit the protection scope of the present application. Although the present application has been described in detail with reference to the above embodiments, those of ordinary skill in the art should understand that the technical solutions of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.

Claims

1. A multilayer current collector, characterized in that: It comprises a base layer and a composite metal layer arranged on at least one side surface of the base layer, wherein the composite metal layer comprises a collector layer and an aluminum layer which are stacked, and the collector layer is located between the base layer and the aluminum layer; The resistivity ρ of the composite metal layer on any one side surface of the multilayer current collector satisfies 2.7Ω·m<ρ≤3.1Ω·m.

2. The multilayer current collector according to claim 1, characterized in that: The aluminum layer <200> The relative texture coefficient of the crystal plane is 30%-60%.

3. The multilayer current collector according to claim 1, characterized in that: The aluminum layer includes a first element, the first element includes at least one of magnesium, calcium, chlorine, and nickel, and the mass proportion of the first element in the aluminum layer is 0.1%-1%.

4. The multilayer current collector according to claim 1, characterized in that: The aluminum layer includes a first aluminum sub-layer, a second aluminum sub-layer and a third aluminum sub-layer which are stacked, and the first aluminum sub-layer is close to the collector layer; Wherein, the resistivity of the first aluminum sub-layer and the resistivity of the third aluminum sub-layer are both greater than the resistivity of the second aluminum sub-layer; The thickness of the aluminum layer×10%≤the thickness of the second sub-aluminum layer<the thickness of the first sub-aluminum layer; The thickness of the aluminum layer×10%≤the thickness of the second aluminum sub-layer<the thickness of the third aluminum sub-layer.

5. The multilayer current collector according to claim 1, characterized in that: The thickness of the aluminum layer is 0.2-5 μm; preferably, the thickness of the aluminum layer is 0.8-2 μm.

6. The multilayer current collector according to claim 1, characterized in that: The thickness of the collector layer is 1%-10% of the thickness of the aluminum layer; the material of the collector layer includes at least one of aluminum, aluminum alloy, nickel, nickel alloy, chromium, chromium alloy, silver, silver alloy, titanium, and titanium alloy.

7. The method for preparing a multilayer current collector according to any one of claims 1 to 6, characterized in that: The steps include: S1, generating the collector layer on the surface of the substrate layer by a magnetron sputtering process to obtain a pretreated substrate layer; S2, forming the aluminum layer on the surface of the pretreated base layer using a molten salt electroplating method.

8. The method for preparing a multilayer current collector according to claim 7, characterized in that: The process parameters of the magnetron sputtering process are as follows: the sputtering power is 6-20kW, the background vacuum is 3×10 -3 -5×10 -3 Pa, argon flow rate is 60-300sccm, the cooling temperature of the sputtering main roller is -35℃ to 0℃, and the winding speed is 5-8m / s.

9. The method for preparing a multilayer current collector according to claim 7, characterized in that: The molten salt electroplating method comprises the following steps: A1, mixing AlCl3, NaCl and KCl to obtain a ternary inorganic salt, heating the ternary inorganic salt, and then performing dehydration and electrolytic decontamination treatment to obtain an inorganic molten salt; A2, placing the pretreated base layer in the inorganic molten salt for electroplating to generate the aluminum layer on the surface of the pretreated base layer.

10. A pole piece, characterized in that: The invention comprises a multi-layer current collector as claimed in any one of claims 1 to 6 and an electrode active material located on the multi-layer current collector.

Citation Information

Patent Citations

  • Current collector and lithium ion battery

    CN112909264A

  • Positive electrode composite aluminum foil current collector and preparation method thereof

    CN117904586A

  • High-strength low-resistance positive electrode composite current collector, preparation method thereof, positive electrode plate and electrochemical device

    CN117936795A

  • Multilayer composite current collector, pole piece and lithium ion battery

    CN119447312A

  • Composite current collector, and preparation method therefor and use thereof

    WO2023245872A1